Situation Report: Romania, 14 April 1976 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. President of Guinea-Bissau in Romania Romanian Media on Chinese Events The Training of Specialists form Developing Countries Intensifying Financial Control Preparations for Forthcoming Trade Union Congress Union of Communist Youth Prepares for Congress on Political Education Controversy and Rivalry in the Field of Popular Music